A tongue tumor as an example of oral cancer in MRI imaging - a case study - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
Magnetic resonance tomography (MR) is a valuable source in the diagnosis of oral cancer due to: obtaining images in any planes and cross-sections, high tissue resolution and not subjecting the patient to ionizing radiation. In this case, presented a 66-year-old man with an advanced visible change in the body of the tongue, symptoms associated with pain and difficulty swallowing, uncomfortable breathing, salivation, and a speech problem underwent MRI examination to determine the location and extent of neoplastic change. According to the World Health Organization (WHO) oral cancer is a global problem and is the sixth most common cancer among all types of cancer. In the last decade, an increase in the percentage of young patients with tongue cancer has been observed.